Middle Ages Christian Colour Precious Stones Symbols in the Context of a new Conception of Symbol as a Synergetic Linguo-Cultural Hyper Sign - Oguy, Oleksandr; Ivasiuk, Olha; Ivasiuk, Galyna (Mediaforum : Analytics, Forecasts, Information Management, 2021)
The article focuses on systematic research of Christian colour precious stones symbols in the context of a new conception of symbol as a synergetic lingo cultural hyper sign. It was pointed out that colours as hyper symbols, which were realized through precious stones, accepted symbolic use typical for Christianity. It was also proved that in Middle Ages colour was an expressive characteristic for precious stones depicting in literature. In general symbols were defined as complicated cultural phenomena depending upon both individual interpretation and upon the level of cultural stereotypes.